Analisis Sistematis Dampak Media Sosial Terhadap Kesejahteraan Mental Remaja - Adinda Naila Apsari D; Usiono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Social media has become an integral part of teens' lives, providing opportunities for social interaction, learning, and entertainment. However, its use also raises concerns regarding its impact on mental well-being. This study aims to conduct a systematic analysis of the literature that discusses the relationship between social media use and adolescent mental well-being. The study identified factors such as the duration of use, the type of platform, as well as specific activity on social media that contributed to both positive and negative outcomes, including anxiety, depression, self-image, and social relationships. The results of the study show that the impact of social media on adolescents is complex, influenced by individual and social contexts. This article provides insights for parents, educators, and policymakers to optimize the healthy use of social media for teens.